Graph Partition Neural Networks for Semi-Supervised Classification - Liao, Renjie; Brockschmidt, Marc; Tarlow, Daniel; Gaunt, Alexander; Urtasun, Raquel; Zemel, Richard S. (Microsoft, 2017)
We present graph partition neural networks (GPNN), an extension of graph neural networks (GNNs) able to handle extremely large graphs. GPNNs alternate between locally propagating information between nodes in small subgraphs and globally propagating information between the subgraphs. To efficiently partition graphs, we experiment with spectral partitioning and also propose a modified multi-seed flood fill for fast processing of large-scale graphs. We extensively test our model on a variety of semi-supervised node classification tasks. Experimental results indicate that GPNNs are either superior or comparable to state-of-the-art methods on a wide variety of datasets for graph-based semi-supervised classification. We also show that GPNNs can achieve similar performance as standard GNNs with fewer propagation steps. Get the sample code on GitHub >